Effects of body mass index on maximal work production capacity and aerobic fitness during incremental exercise - Ozcelik, O; Aslan, M; Ayar, A; Kelestimur, H (Acad Sciences Czech Republic, Inst Physiology, 2004)
The aim of this study was to investigate the relationship between cardiopulmonary fitness as indicated by maximal work rate (Wmax) production and aerobic capacities (W-AT), body mass index (BMI) and heart rate reserve. A total of 60 sedentary subjects (30 males, 30 females, aged 18-25 years) were enrolled in the study. Each subject performed an incremental exercise test (15 W/min) to the limit of tolerance on an electromagnetically-braked cycle ergometer. There was a negative correlation between increased BMI to Wmax capacity per kilogram body weight in male (r=-0.846, P=0.0001) and in female (r=-0.896, P=0.0001) subjects. In addition, WAT for each kilogram body weight also negatively correlated with increased BMI in male (r=-0.870, P=0.0001) and in females (1-0.807, P=0.0001). The heart rate reserve correlated negatively with increasing BMI: r=-0.699, P=0.0001 (males) and r=-0.655, P=0.0001 (females). The results of the present study have suggested that, due to the inverse correlation between BMI, Wmax capacity, aerobic fitness and heart rate reserve, it may be useful to consider BMI in establishing cardiopulmonary fitness in various subjects.
Keywords: body mass index; exercise test; aerobic fitness